PERAN MANAJEMEN KEPEMIMPINAN KEPALA SEKOLAH DALAM PENERAPAN MEDIA PEMBELAJARAN NOTEBOOKLM BERBASIS AI DI SMK NEGERI 1 AIR PUTIH - Hammuda Sitorus; Nizwardi Jalinus; Ernawati; Elfi Tasrif (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the role of school principal leadership management in driving the implementation of NotebookLM as an AI-based interactive learning media at SMK Negeri 1 Air Putih, Batu Bara Regency. NotebookLM, developed by Google, is an Artificial Intelligence platform that enables educators to produce diverse interactive learning materials, including presentations, quizzes, concept maps, and animated podcast videos. Using a qualitative descriptive approach, this research collected data through observation, in-depth interviews with the school principal, teachers, and students, as well as documentation analysis. Findings reveal that transformational and visionary leadership by the school principal was the primary catalyst in successfully adopting NotebookLM into classroom instruction. The principal's strategic role encompassed policy formulation, teacher capacity building through training, provision of digital infrastructure, and motivational supervision. The implementation of NotebookLM, particularly the animated podcast video contextualizing learning materials to students' daily lives, significantly elevated student enthusiasm and motivation. The research concludes that effective leadership management is a decisive determinant in the successful integration of AI-based educational technology in vocational high schools.